2022
DOI: 10.46336/ijrcs.v3i1.185
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Manual Processing Of Blood Clamps Waste into Chitosan Powder

Abstract: Blood clams (Anadara granosa) are endemic clams found in Southeast Asia and East Asia. Blood clams are widely consumed by the public as seafood dishes in coastal food stalls. The great potential of blood clams will increase the waste of clam shells produced. The accumulation of shellfish waste will cause pollution and reduce environmental aesthetics. The chitin content in blood clam shells can be used as chitosan. Chitosan is a polymer of -(1-4) glucosamine which is formed when the acetyl group in chitin is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This chitosan (shellfish) contains calcium carbonate (CaCO3), which when heated, will turn into CaO (3.04 %) and release CO2 into the air, leaving only CaO (quicklime) and Si (Silica), whose content is a cement-forming component other than Fe2O3 (ferric oxide) and AL2O3. Chitosan iresults fromthe chitin deacetylation process by removing the acetyl group to obtain polymer compounds and glucosamine [12]. The preliminary observation by ITS Chemical Laboratory in 2019, also found that chitosan has Silicon Oxide -SiO2 (17,98 %), which affects stability and viscosity.…”
Section: Fillermentioning
confidence: 99%
See 1 more Smart Citation
“…This chitosan (shellfish) contains calcium carbonate (CaCO3), which when heated, will turn into CaO (3.04 %) and release CO2 into the air, leaving only CaO (quicklime) and Si (Silica), whose content is a cement-forming component other than Fe2O3 (ferric oxide) and AL2O3. Chitosan iresults fromthe chitin deacetylation process by removing the acetyl group to obtain polymer compounds and glucosamine [12]. The preliminary observation by ITS Chemical Laboratory in 2019, also found that chitosan has Silicon Oxide -SiO2 (17,98 %), which affects stability and viscosity.…”
Section: Fillermentioning
confidence: 99%
“…Chitosan (shellfish) is the shell of a mollusk. This chitosan (shellfish) contains calcium carbonate (CaCO3), which, when heated, will turn into CaO (3.04 %) [12]. From the preliminary observation by ITS Chemical Laboratory in 2019, it was also found that chitosan contains Silicon Oxide -SiO2 (17.98), which affects stability and viscosity to increase the value of marshall characteristics.…”
Section: Introductionmentioning
confidence: 99%